Reconsidering the Mental Health of Women. A Scoping Review of Poly Cystic Ovary Syndrome and Meditation Therapies - Khan, Saeeda; Punjwani, Sumaira Khowaja; Badil (Indus Journal of Bioscience Research, 2025)
Background: A complex heterogeneous endocrine issue linked to female reproductive disorder is known as polycystic ovarian syndrome. It has been shown that a lot of cysts form in the female ovarian antral follicles when there is an imbalance in the sex hormones. Method: Scoping review methodology was used. For which an extensive literature review was carried out comprehensively from April to September 2024. Databases were used to search the literature: PsycINFO, CINHAL, Medline, and PubMed and Google scholar from 2019 to 2024, using various keywords and Boolean operators. Objective: To identify, synthesize, evaluate the evidences that PCOS effect mental health of women and Mindfulness Training Program (MTP) can improve level of stress, anxiety and depression. Results: Subsequent the elimination of duplicates, 185 independent studies from the 352 records that the search technique produced were suitable for title and abstract screening. Following a successful full-text retrieval of 82 citations, out of which 26 retrieval citation met the inclusion criteria and were incorporated into the analysis. Examined were a number of psychological effects, such as anxiety, depression, stress, concerns about PCOS, and general psychological distress. Discussion: The Scoping review offers a brief summary of the data currently available about MTP’s effectiveness in reducing PCOS symptoms. The results help shape the direction of current and upcoming studies in this area. Further investigations must improve the current monitoring status concerning MTP delivery. Conclusion: The analysis suggests that there is an urgent need for significant advancements in PCOS research concerning mental health assessment and therapies.